Investigations on the fragmentation and ionization of endohedral fullerenes using synchrotron radiation - Hellhund, Jonas; Justus Liebig University Giessen (My University, 2015)
Cross-section measurements employing the photon-ion merged-beam technique for photoionization and photofragmentation of ions of endohedral fullerenes Xe@C60 and Lu3N@C80 exposed to synchrotron-generated extreme ultraviolet light and soft x-rays are presented. A part of the required Xe@C60 material was synthesized with the production apparatus available at the Institute for Atomic and Molecular Physics (IAMP) in Gießen. A list of modifications to apparatus and production methods facilitated an increase in the endohedral yield by a factor of 30.Xe@C60 measurements were carried out at the synchrotron facility Advanced Light Source (ALS) at the Lawrence Berkeley National Laboratory (LBNL) in Berkeley. The current study extends previous efforts on single and double ionization of Xe@C60+ as well as fragmentation channels towards triple ionization with fragmentation of Xe@C60+ and towards double ionization with fragmentation of negative Xe@C60- ions in the photon energy range 60-150 eV. The relative cross-section data were normalized to absolute measurements either directly or the relative cross sections were scaled to match absolute cross-section data of pristine fullerenes in the respective channels at energies where the encapsulated xenon does not contribute. The excess cross section due to the encapsulated atom is determined by comparison of pristine and endohedral fullerene. The experimental results are compared to previously published measurements for Xe@C60+ double ionization.Relative cross-section measurements for Lu3N@C80 were carried out at the synchrotron facility PETRAIII of the Deutsches Elektronen-Synchrotron (DESY) in Hamburg. Prominent structures related to the carbon K-shell ionization threshold were observed in the energy range 280-330 eV. These resonance structures have been analyzed in seven product channels and are compared with previously known absorption spectra of several fullerene species. Unlike for Xe@C60, no signatures of the encapsulated atoms have been found particularly searching for the N-1s and Lu-3d thresholds in the energy ranges 390-435 eV and 1500-1700 eV. The carbon K-shell threshold seen in double ionization of Lu3N@C80^2+ is shifted by Delta E = (2.90+-0.24) eV with respect to the carbon K-shell threshold in double ionization of Lu3N@C80 +. The shift is explained by the difference in the Coulomb potentials of singly and doubly charged and Lu3N@C80. An outer endohedral fullerene radius R=(5.0+-0.4) x 10^-10 m is inferred. Comparison with Sc3N@C80 indicates that Lu3N has an identical influence on the C80 behavior at the carbon K-shell as Sc3N.

Wirkungsquerschnitte für die Photoionisation und Photofragmentation der endohedralen Fullerene Xe@C60 und Lu3N@C80 durch Synchrotronstrahlung im Energiebereich zwischen extrem ultravioletten Licht und weicher Röntgenstrahlung, gemessen mit der sogenannten Photon-Ion merged-beams Methode , werden gezeigt. Ein Teil des dafür erforderlichen Xe@C60-Materials wurde an der Produktionsapparatur synthetisiert, die im Gießener Institut für Atom- und Molekülphysik (IAMP) vorhanden ist. Eine Reihe von Modifikation an Apparatur und Herstellungsmethodik ermöglichte eine Steigerung des endohedralen Anteils im Material um den Faktor 30.Die Messungen mit Xe@C60 wurden an der Synchrotronlichtquelle Advanced Light Source (ALS) des Lawrence Berkeley National Laboratory (LBNL) in Berkeley durchgeführt. Die vorliegende Studie knüpft an vorhergehende experimentelle Forschung auf dem Gebiet von Einfach- und Doppelionisation von Xe@C60+ - Ionen sowie deren Fragmentationskanälen an und erweitert die Untersuchungen auf die Dreifachionisation sowie Fragmentation von Xe@C60+ - Ionen und auf die Doppelionisation sowie Fragmentation negativer Xe@C60- - Ionen im Energiebereich 60-150 eV. Relative Wirkungsquerschnitte wurden entweder direkt anhand von Absolutmessungen normiert oder indem sie an absolute Messdaten von regulären, d.h. nicht-endohedralen, Fullerenen in Energiebreichen angepasst wurden, wo nur der Fullerenkäfig, nicht aber das eingeschlossene Atom, zum Wirkungsquerschnitt beiträgt. Die vom eingeschlossenen Atom verursachte Überhöhung des Wirkungsquerschnitts wurde durch einen Vergleich zwischen den Spektren von endohedralen und leeren Fullerenen ermittelt. Die experimentellen Ergebnisse werden weiterhin mit bereits publizierten Ergebnissen für die Doppelionisation von Xe@C60+ verglichen.Die relativen Wirkungsquerschnitte von Lu3N@C80 wurden an der Synchrotronlichtquelle PETRAIII des Deutschen Elektronen-Synchtrotrons (DESY) in Hamburg gemessen. Dabei wurden markante Strukturen im Energiebereich 280-330 eV beobachtet, die mit der Kohlenstoff-K-Ionisationsschwelle zusammenhängen. Die Resonanzstrukturen wurden in sieben verschiedenen Reaktionskanälen analysiert und mit bereits bekannten Spektren anderer Fullerenspezies verglichen. Anders als bei Xe@C60 konnten für Lu3N@C80 keine Hinweise auf die N-1s- und Lu-3d-Ionisationsschwellen der eingeschlossenen Atome in den Energiebereichen 390-435 eV und 1500-1700 eV gefunden werden. Die Kohlenstoff-K-Kante tritt in der Doppelionisation von Lu3N@C802+ um Delta E = (2.90+-0.24) eV verschoben gegenüber ihrer Energie in der Doppelionisation von Lu3N@C80+ auf. Diese Verschiebung wird anhand des unterschiedlichen Coulomb-Potentials der unterschiedlichen Ladungszustände erklärt. Mittels der Verschiebungsenergie wird auf einen äußeren Fulleren-Radius R = (5.0+-0.4) x 10^-10 m geschlossen. Aus Messungen mit Sc3N@C80 ergibt sich die Vermutung, dass das eingeschlossene Molekül Lu3N den gleichen Einfluss auf den C80-Käfig ausübt, wie Sc3N.
Untersuchungen zur Fragmentation und Ionisation endohedraler Fullerene durch Synchrotronstrahlung
Keywords: endohedrale Fullerene; Photoionisation; Photofragmentation; Synchrotronstrahlung; Synthese endohedraler Fullerene; endohedral fullerenes; photoionization; photofragmentation; synchrotron radiation; endohedral fullerene synthesis; ddc:530